2013
DOI: 10.2298/sarh1312744v
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic dental injuries in Serbian children: Epidemiological study

Abstract: Dental injuries in preschool children most frequently resulted from fall at home. Schoolchildren most frequently injured teeth outdoor during play. Violence and sport injuries were most frequent cause of injury in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…4,9,1316 However, the therapeutic role of VIP in managing UC is still not well established and conflicting findings have been reported. 17,18 The labile peptide VIP undergoes rapid degradation once administered systemically; therefore, delivering the required amounts of the peptide to the target site becomes challenging. 19 In order to be effective in vivo, the free VIP needs to be administered parenterally at higher doses and with increased frequency, which results in severe toxicities such as hypotension and tachycardia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,9,1316 However, the therapeutic role of VIP in managing UC is still not well established and conflicting findings have been reported. 17,18 The labile peptide VIP undergoes rapid degradation once administered systemically; therefore, delivering the required amounts of the peptide to the target site becomes challenging. 19 In order to be effective in vivo, the free VIP needs to be administered parenterally at higher doses and with increased frequency, which results in severe toxicities such as hypotension and tachycardia.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory properties of VIP have been demonstrated in animal models of several immune disorders such as septic shock, multiple sclerosis, rheumatoid arthritis (RA), , and CD. , During severe inflammation in the intestine, levels of VIP and its receptors are known to be down-regulated. , Furthermore, VIP knockout mice show profound abnormalities along the GI tract, indicating the importance of VIP in health and disease of the intestine . VIP has also been studied as a potential candidate for the management of CD in animal models and has shown promising results. ,, However, the therapeutic role of VIP in managing UC is still not well established and conflicting findings have been reported. , The labile peptide VIP undergoes rapid degradation once administered systemically; therefore, delivering the required amounts of the peptide to the target site becomes challenging . In order to be effective in vivo, the free VIP needs to be administered parenterally at higher doses and with increased frequency, which results in severe toxicities such as hypotension and tachycardia. , Thus, one important reason for variability in the previous studies could be explained by potential variations in the administered VIP reaching the sites of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the place of injury, our results revealed that during office-hours injuries occurred more commonly in school and kindergarten, which was expected. 24 Having in mind that these variables were not independent risk factors for unfavorable outcome, differences in the place of occurrence, mechanism, and cause of injury were marked as insignificant findings, and were not regarded as factors that contributed to poorer outcomes of after-hours TDI.…”
Section: Discussionmentioning
confidence: 99%